2008
DOI: 10.1080/10826080802344625
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Xylometazoline Nasal Drops by Inhalation

Abstract: Six male prisoners who misused xylometazoline nasal drops by inhalation were interviewed by a prison physician in 2006. The prisoners received xylometazoline drops during regular visits in the prison ambulatory service. In order to get the medication, the subjects reported false symptoms of rhinosinusitis and allergic reactions. Psychoactive effects of inhaled xylometazoline were described as "stimulation," "excitation," and "feeling of strength." Although preliminary, our findings suggest that topical adrener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Anand J.S. et al [24] reported a case of psychoactive effects in six prisoners when xylometazoline was inhaled. The inmates simulated a runny nose, sinusitis, and allergic rhinitis to accumulate an appropriate dose of ND.…”
Section: Diagnosis Of the Rhinitis Medicamentosa Is Based On The Nasa...mentioning
confidence: 99%
“…Anand J.S. et al [24] reported a case of psychoactive effects in six prisoners when xylometazoline was inhaled. The inmates simulated a runny nose, sinusitis, and allergic rhinitis to accumulate an appropriate dose of ND.…”
Section: Diagnosis Of the Rhinitis Medicamentosa Is Based On The Nasa...mentioning
confidence: 99%